Dessmond Doss’ Struggle in Defending his Value in “Hacksaw Ridge” Movie - Aulia Putri; M. Maulana Saifurrohman (English Department, University of Riau Kepulauan, Batam,Indonesia, 2018)
This study describes struggles of a man named Desmond Doss in “Hacksaw Ridge” movie. This movie tells about a man in his World War II experiences. Doss rolled as an American pacificist combat medic who was a Seventh-day Adventist Christian. It was directed by Mel Gibson and written by Robert Schenkkan and Andrew Knight. This study has some objectives; to identify the way Doss defends his value in the movie and to identify kinds of struggles that Doss do in defending his value in the movie. In addition, it is to describe three disrespect forms that happen to the main character in “Hacksaw Ridge” Movie. This study is qualitative research because it analyzed the descriptive data based on the conversations in “Hacksaw Ridge” movie. The data are collected from MP4 video and the script of “Hacksaw Ridge” movie. It is found the struggle of Doss that causes a violation on his body, the struggle of Doss that makes all of his rights denied, and the struggle of Doss that makes his way of life affected by other people.